XVIII amžiaus antrosios pusės Lietuvos Didžiosios Kunigaikštystės universalieji laikmačiai: Vilniaus ir Gardino kalendoriai - Žąsinaitė-Gedminienė, Jurgita (Literatūra, 2010)
The article focuses on the calendars of the Grand Duchy of Lithuania (GDL) which were published in the second half of the 18th century. Emphasizing the fact that in the Age of Enlightenment calendars as well as other periodicals underwent significant developments in terms of form, content, and audience,Vilnius Calendar (pl. Kalendarz Wileński) and Grodno Calendar (Kalędarz Grodzieński) are being analysed. Vilnius and Grodno Calendars included news from the whole world and from the area of the GDL. The information concerning astronomy, medicine, and prophesies also used to be published there. The calendars dealt with social and moral issues of the time and were considered to be peculiar instructors of the society. Apart from that they enabled their readers to express themselves by proclaiming openly society’s interests and needs. In this way a specific communication medium between this universal form of press and its audience was created. From the publications of Vilnius and Grodno Calendars the history of Lithuanian post could be traced. There is also much information of the state management in the GDL in the last decades of the 18th century. In general Vilnius and Grodno Calendars could be regarded as some ABC books of politics, economy, and culture that were dedicated to the inquisitive and demanding society of the second half of the 18th century.